Adnexal torsion: is there a familial tendency? - N. Smorgick; O. Nir; M. Pekar-Zlotin; S. Maymon; Y. Melcer; R. Maymon (IMR Press, 2020)
Objective: To investigate whether patients diagnosed with adnexal torsion report a family history of adnexal torsion in a first degree relative. Materials and Methods: All women with a surgical diagnosis of adnexal torsion operated from 2008 to 2016 were contacted for participation in the study. The study was conducted by a telephone questionnaire. In addition, the medical records were retrospectively reviewed and information on demographic characteristics, surgical findings at time of torsion, and history of recurrent torsion events were collected. Results: Two hundred thirty women with a surgical diagnosis of adnexal torsion were identified. Of these, 147 women were reached and agreed to participate in the study. A history of adnexal torsion in a first degree relative was reported by seven (4.8%) patients: three cases involved an adnexal torsion event in a sister, and four cases involved an adnexal torsion event in a mother or daughter. Patients with a positive family history of adnexal torsion were more likely to experience torsion of otherwise normal adnexa without adnexal cysts compared to those with a negative family history (71.4% vs. 27.1%, p = 0.01) and to report recurrent torsion events (57.1% vs. 17.1%, p = 0.009). Conclusion: A family history of adnexal torsion in a first degree relative is found in a minority of cases and is significantly associated with torsion of otherwise normal adnexa and with recurrent torsion events. Thus, patients with a family history of torsion may be considered a high-risk subgroup of patients.